Virtuous organizations: Desire, consumption and human flourishing in an era of climate change - Moore, Geoff (Frontiers in Sociology, 2022)
The notion of virtuous organizations has an established place in the business ethics/organization studies literature. But this conceptualization drew principally on Alasdair MacIntyre's After Virtue. His more recent work Ethics in the Conflicts of Modernity, with its focus on desire, consumption and human flourishing, demands a revisiting of the original concept. The first aim of this paper, therefore, is to provide an extended theory of the notion of the virtuous organization. An obvious application of this extended theory is to the issue of climate change. In exploring this, the paper has a further aim which is to respond to Banerjee et al.'s call for more theory building that articulates post-growth possibilities at the organization level in relation to the multiple challenges which society faces in response to the changing climate. The paper begins by summarizing the current conceptual framework of the virtuous organization while recognizing critiques of MacIntyre's work and its organizational application. It then turns to the issues of desire and consumption highlighted in MacIntyre's latest book, drawing also on an extended literature in these areas including insights from Girard's work, and concluding with MacIntyre's contentions in relation to human flourishing. This leads to the extended conceptual framework which is then applied to the issue of climate change. The particular theoretical contribution of the paper is to understand virtuous organizations as playing an important role in the redirection and re-education of desires, leading to the pursuit of goods that we have good reason to desire, and so to the good for individuals and communities, and ultimately to human flourishing within ecological limits. The similarities with and differences from the degrowth/post-growth movement are explored to demonstrate the distinctive contribution a MacIntyrean approach makes. The practical implications of this theoretical contribution are then spelled out, including a consideration of the potential ubiquity or otherwise of this approach, before conclusions are drawn.